Means testing as screening for financial assistance for tertiary level education (TLE) in Trinidad and Tobago - Hosein, R. (2005)
Argues that tertiary level improvement can make a vital contribution to the economic growth process in Trinidad and Tobago. Notes however that the state should seek to implement a financial assistance programme which is both vertically and horizontally efficient as compared to a lump sum subsidiary which is typically riddled with vertical inefficiency.